ANALISIS KINERJA KEUANGAN DALAM MENDUKUNG OPERASI PERUSAHAAN PADA PT. TRI SAPTA JAYA CABANG SIBOLGA - Elisabet Tamba; Yacub Hutabarat; Tiurlina Hasmawati Sihite (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
Financial reports are a very important tool for obtaining information regarding the financial position and results achieved by the company. The purpose of this study was to determine the Financial Performance Analysis Can Support Company Operations at PT. Tri Sapta Jaya Sibolga Branch. the formulation of the research hypothesis is: Financial Performance Analysis Can Support Company Operations At PT. Tri Sapta Jaya Sibolga Branch. The population in this study are all financial statements and profit and loss balance of PT. Tri Sapta Jaya Sibolga Branch. The sample in this study is financial report data and profit and loss balance for the last 3 years, namely 2019 to 2021. The data used is secondary data. The research results show that the Liquidity Ratio in 2019 is known to be 1.06%, in 2020 it is 1.07%, in 2020 of 1.08% Activity ratio in 2019 of 11 times, in 2020 of 19 times, and in 2021 of 18 times. Profitability Ratio Analysis found that the Gross profit margin in 2019 was 4.69% The Gross profit margin in 2020 was 5.3% The Gross profit margin in 2021 was 5.3% 1.09%, in 2021 it will be 1.16%,